Multistrain Probiotics Alleviate Diarrhea by Modulating Microbiome-Derived Metabolites and Serotonin Pathway - Jin-Ju Jeong; Yoo-Jeong Jin; Raja Ganesan; Hee Jin Park; Byeong Hyun Min; Min Kyo Jeong; Sang Jun Yoon; Mi Ran Choi; Satya Priya Sharma; You Jin Jang; Uigi Min; Jong-Hyun Lim; et al. (Probiotics and Antimicrobial Proteins, 2025)
Diarrhea, a common gastrointestinal symptom in health problems, is highly associated with gut dysbiosis. The purpose of this study is to demonstrate the effect of multistrain probiotics (Sensi-Biome) on diarrhea from the perspective of the microbiome-neuron axis. Sensi-Biome ( Lactiplantibacillus plantarum , Bifidobacterium animalis subsp. lactis , Lactobacillus acidophilus , Streptococcus thermophilus , Bifidobacterium bifidum , and Lactococcus lactis ) was administered in a 4% acetic acid–induced diarrhea rat model at concentrations of 1 × 10 8 (G1), 1 × 10 9 (G2), and 1 × 10 10 CFU/0.5 mL (G3). Diarrhea-related parameters, inflammation-related cytokines, and stool microbiota analysis by 16S rRNA were evaluated. A targeted and untargeted metabolomics approach was used to analyze the cecum samples using liquid chromatography and orbitrap mass spectrometry. The stool moisture content ( p < 0.001), intestinal movement rate ( p < 0.05), and pH ( p < 0.05) were significantly recovered in G3. Serotonin levels were decreased in the multistrain probiotics groups. The inflammatory cytokines, serotonin, and tryptophan hydroxylase expression were improved in the Sensi-Biome groups. At the phylum level, Sensi-Biome showed the highest relative abundance of Firmicutes . Short-chain fatty acids including butyrate, iso-butyrate, propionate, and iso-valeric acid were significantly modified in the Sensi-Biome groups. Equol and oleamide were significantly improved in the multistrain probiotics groups. In conclusion, Sensi-Biome effectively controls diarrhea by modulating metabolites and the serotonin pathway.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Association between TGF-β/BMP signaling pathway polymorphisms and the risk of primary ovarian insufficiency in Korean women - Yong Hyun Ha; Ji Hyang Kim; Chang Soo Ryu; Ji Won Kim; Eun Ju Ko; Jeong Yong Lee; Ji Eun Shin; Young Ran Kim; Eun Hee Ahn; Nam Keun Kim (Genes & Genomics, 2024)

Relationship between PM1.0 and PM2.5 in urban and background areas of Republic of Korea - Sujin Kwon; Soo Ran Won; Hyung Bae Lim; Sung Chul Hong; Yong Mi Lee; Ji Yun Jung; Sung-Deuk Choi; Sang-Jin Lee; Seungmee Oh; Ju Young Kim; Yong Pyo Kim; Hye Jung Shin; et al. (Atmospheric Pollution Research, 2023)

Establishment of a qualified ex vitro-acclimatized whole plant reproduction system using secondary somatic embryos in Panax ginseng - Ju Hee Kim; Mi Young Kim; Jae Hyun Lee; Jang Uk Kim; Ok Ran Lee (Plant Biotechnology Reports, 2023)

Neuroanatomical distribution of galectin-3 in the adult rat brain - Hong-Il Yoo; Eu-Gene Kim; Eun-Jin Lee; Sung-Young Hong; Chi-Sun Yoon; Min-Ju Hong; Sang-Jin Park; Ran-Sook Woo; Tai-Kyoung Baik; Dae-Yong Song (Journal of Molecular Histology, 2017)

Insecticide resistance and cytochrome-P450 activation in unfed and blood-fed laboratory and field populations of Culex pipiens pallens - Kyu-Sik Chang; Heung-Chul Kim; Terry A. Klein; Young Ran Ju (Journal of Pest Science, 2017)

Acaricidal activity of Asarum heterotropoides root-derived compounds and hydrodistillate constitutes toward Dermanyssus gallinae (Mesostigmata: Dermanyssidae) - Jun-Ran Kim; Haribalan Perumalsamy; Ju-Hee Lee; Young-Joon Ahn; Young Su Lee; Sang-Guie Lee (Experimental and Applied Acarology, 2016)

Memory Impairment in Estrogen Receptor α Knockout Mice Through Accumulation of Amyloid-β Peptides - Chul Ju Hwang; Hyung-Mun Yun; Kyung-Ran Park; Ju Kyung Song; Hyun Ok Seo; Byung Kook Hyun; Dong Young Choi; Hwan-Soo Yoo; Ki-Wan Oh; Dae Yeun Hwang; Sang-Bae Han; Jin Tae Hong (Molecular Neurobiology, 2015)

Mercury contamination and exposure assessment of fishery products in Korea - Hye-Ran Yang; Na-Young Kim; Lae-Hong Hwang; Ju-Sung Park; Jung-Hun Kim (Food Additives & Contaminants Part B-Surveillance, 2015)

Toxicity assessment of a novel silk fibroin and poly-methyl-methacrylate composite material - Min Ju Chae; Dae Won Kim; Yun Joong Kim; Hae Yong Kweon; Yong-Jun Cho; Soo Young Choi; Hae Ran Lee (Molecular & Cellular Toxicology, 2014)

Plant-derived mAbs have effective anti-cancer activities by increasing ganglioside expression in colon cancers - Jae-Sung Ryu; Ju-Taek Lee; Malg-Um Lim; Mi-Ran Hwang; Kyung-A Hwang; Young-Ho Cho; Jeong-Hwan Lee; Kisung Ko; Young-Kug Choo (Biotechnology Letters, 2013)

Molecular characterization of KGH, the first human isolate of rabies virus in Korea - Jun-Sun Park; Chi-Kyeong Kim; Su Yeon Kim; Young Ran Ju (Virus Genes, 2013)

First complete genomic characterization of two tick-borne encephalitis virus isolates obtained from wild rodents in South Korea - Seok-Min Yun; Su Yeon Kim; Young Ran Ju; Myung Guk Han; Young Eui Jeong; Jungsang Ryou (Virus Genes, 2011)

Molecular characterization of a cysteine proteinase inhibitor, PgCPI, from Panax ginseng C. A. Meyer - Dae-Young Jung; Ok Ran Lee; Yu-Jin Kim; Jung-Hye Lee; Rama Krishna Pulla; Gayathri Sathiyaraj; Ju-Sun Shim; Deok-Chun Yang (Acta Physiologiae Plantarum, 2010)

Engineering the Japanese encephalitis virus RNA genome for the expression of foreign genes of various sizes: Implications for packaging capacity and RNA replication efficiency - Sang-Im Yun; Yu-Jeong Choi; Xiao-Fang Yu; Jae-Young Song; Young-Hak Shin; Young-Ran Ju; Seok-Yong Kim; Young-Min Lee (Journal of NeuroVirology, 2007)

In vitro and in planta Interaction Evidence between Nicotiana tabacum Thaumatin-Like Protein 1 (TLP1) and Cucumber mosaic virus Proteins - Min Jung Kim; Byung-Kook Ham; Hwa Ran Kim; In-Ju Lee; Young Jin Kim; Ki Hyun Ryu; Young In Park; Kyung-Hee Paek (Plant Molecular Biology, 2005)

The polymorphisms of Tim-1 promoter region are associated with rheumatoid arthritis in a Korean population - Soo-Cheon Chae; Young-Ran Park; Ju-Hee Song; Seung-Cheol Shim; Kyung-Sik Yoon; Hun-Taeg Chung (Immunogenetics, 2005)